Perancangan Sistem Informasi Penerimaan Siswa Baru Berbasis Web Pada SMK Bhakti Pertiwi Kota Tangerang - Andri Ansah; Ika Yuniva; Haruman Dinar Sanjaya (Indonesian Journal of Networking and Security (IJNS), 2019)
SMK Bhakti Pertiwi is one of the private Vocational Schools in Tangerang City, of course, as an educational institution, of course, it is also expected to keep up with technological developments, because for tens of years SMK Bhakti Pertiwi was established, new student data processing systems still use manual methods. As for some of the problems that are often faced by the new admissions committee when conducting a manual admission system include: Registration forms are often tucked / lost / wrong when placed in a folder that is in place so that when needed for re-registration it often takes time other than that it will cause delays in reporting, inaccurate recording of student data, especially those with somewhat similar names, etc. For this reason, the author tries to make a final assignment regarding the new student admission system at the Bhakti Pertiwi Vocational School, Tangerang City, which until now has not been computerized. Web-based information systems can be used as a means of improving the new student admission system. The utilization will facilitate a job such as recording, storing, searching and processing data faster so that the decisions taken are more appropriate, saving costs and time both for the committee and for the registrant